Berberine Is a Novel Type Efflux Inhibitor Which Attenuates the MexXY-Mediated Aminoglycoside Resistance in Pseudomonas aeruginosa - Morita, Yuji; Nakashima, Ken-ichi; Nishino, Kunihiko; Kotani, Kenta; Tomida, Junko; Inoue, Makoto; Kawamura, Yoshiaki (Frontiers in Microbiology, 2016)
The emergence and spread of multidrug-resistant P. aeruginosa infections is of great concern, as very few agents are effective against strains of this species. Methanolic extracts from the Coptidis Rhizoma (the rhizomes of Coptis japonica var. major Satake) or Phellodendri Cortex (the bark of Phellodendron chinense Schneider) markedly reduced resistance to anti-pseudomonal aminoglycosides (e.g., amikacin) in multidrug-resistant P. aeruginosa strains. Berberine, the most abundant benzylisoquinoline alkaloid in the two extracts, reduced aminoglycoside resistance of P. aeruginosa via a mechanism that required the MexXY multidrug efflux system; berberine also reduced aminoglycoside MICs in Achromobacter xylosoxidans and Burkholderia cepacia, two species that harbor intrinsic multidrug efflux systems very similar to the MexXY. Furthermore this compound inhibited MexXY-dependent antibiotic resistance of other classes including cephalosporins (cefepime), macrolides (erythromycin), and lincosamides (lincomycin) demonstrated using a pseudomonad lacking the four other major Mex pumps. Although phenylalanine-arginine beta-naphthylamide (PAβN), a well-known efflux inhibitor, antagonized aminoglycoside in a MexXY-dependent manner, a lower concentration of berberine was sufficient to reduce amikacin resistance of P. aeruginosa in the presence of PAβN. Moreover, berberine enhanced the synergistic effects of amikacin and piperacillin (and vice versa) in multidrug-resistant P. aeruginosa strains. Thus, berberine appears to be a novel type inhibitor of the MexXY-dependent aminoglycoside efflux in P. aeruginosa. As aminoglycosides are molecules of choice to treat severe infections the clinical impact is potentially important.